Acid silage of tuna viscera: Production, composition, quality and digestibility - Banze, Jorge Filipe; da Silva, Maria Fernanda Oliveira; Enke, Dariane Beatriz Schoffen [UNESP]; Fracalossi, Débora Machado (Boletim do Instituto de Pesca, 2017)
Fish waste processed in the form of silage may constitute an alternative to the use of fishmeal (FM). In this study the composition and quality of the acid silage produced from tuna viscera (TV) were characterized and the digestibility of the nutrients of this product was determined for jundia Rhamdia quelen, using ytrium oxide as an inert marker and a completely randomized design. At the end of thirty days, 61.74% of the crude protein of TV was solubilized. Acid silage from TV presented good nutritional composition (high protein, good amino acid profile and essential fatty acids) and good microbiological quality. Crude protein digestibility was similar (88.52%) for TV and FM, but dry matter digestibility was higher (P<0.05) for (TV) (92.20%). Tuna silage presented as a high nutritional quality and nutrient digestibility for jundiá juveniles, R. quelen. Therefore, this novel ingredient has potential as an alternative protein source in aquafeeds.
Silagem ácida de vísceras de atum: Produção, composição, qualidade e digestibilidade
Keywords: Fish waste; Hydrolysis; Protein solubility; Rhamdia quelen